2016
DOI: 10.1101/048900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C4photosynthesis and climate through the lens of optimality

Abstract: 1 CO 2 , temperature, water availability and light intensity were all potential selective pressures to 2 propel the initial evolution and global expansion of C 4 photosynthesis over the last 30 million 3 years. To tease apart how the primary selective pressures varied along this evolutionary 4 trajectory, we coupled photosynthesis and hydraulics models while optimizing photosynthesis 5 over stomatal resistance and leaf/fine-root allocation. We further examined the importance of 6 resource (e.g. nitrogen) reall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 55 publications
(8 reference statements)
1
57
1
Order By: Relevance
“…CO2 generally decreased through this period. Water limitation drove the earliest origin of C4 30 MYA (Christin et al 2008, Zhou et al 2018) and there was a more intense selective pressure for water transport safety, which led to higher decrease of Kleaf in older lineages; however, the role played by water limitation was weakened and replaced by low CO2 and high light as the CO2 decreased with the multiple C4 origins around 5-8 MYA (Zhou et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CO2 generally decreased through this period. Water limitation drove the earliest origin of C4 30 MYA (Christin et al 2008, Zhou et al 2018) and there was a more intense selective pressure for water transport safety, which led to higher decrease of Kleaf in older lineages; however, the role played by water limitation was weakened and replaced by low CO2 and high light as the CO2 decreased with the multiple C4 origins around 5-8 MYA (Zhou et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We used our mechanism-based physiological model from Zhou et al (2018) to consider how the evolution of higher Kleaf would affect the optimal gs and photosynthesis in C3 and C4 plants. An increase in Kleaf in the C3 ancestor selects for higher gs and increases the steady-state leaf water potential to a limited extent ( Fig.…”
Section: Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…Although Jmax/Vcmax has been empirically measured in numerous C3 species (Wullschleger, 1993) and optimal Jmax/Vcmax has been modeled for C3 (Walker et al, 2014;Kromdijk and Long, 2016;Quebbeman and Ramirez, 2016), there have been few measurements in C4, and we are not aware of any theoretical optimality predictions. For C4 species, the assimilation rate would be mostly limited by the light reactions (Baker and Long, 1988;Pearcy and Ehleringer, 1984;Collatz et al, 2992) and there would be a redundancy in RuBP carboxylation if a C3-like Jmax/Vcmax was maintained (Zhou et al, 2018). Furthermore, Zhou et al (2018) showed that if nitrogen is reallocated from the CB cycle to the light reactions, which results in a higher Jmax/Vcmax, C4 assimilation rates will increase significantly in almost all environmental conditions.…”
mentioning
confidence: 99%
“…For C4 species, the assimilation rate would be mostly limited by the light reactions (Baker and Long, 1988;Pearcy and Ehleringer, 1984;Collatz et al, 2992) and there would be a redundancy in RuBP carboxylation if a C3-like Jmax/Vcmax was maintained (Zhou et al, 2018). Furthermore, Zhou et al (2018) showed that if nitrogen is reallocated from the CB cycle to the light reactions, which results in a higher Jmax/Vcmax, C4 assimilation rates will increase significantly in almost all environmental conditions. In C3 plants, Jmax/Vcmax should vary along with different environmental factors (temperature, CO2, light, and water availability; Onoda et al, 2005;Rodriguez-Calcerrada et al, 2008;Kromdijk and Long, 2016;, and we expect the same for C4.…”
mentioning
confidence: 99%